Penilaian Kinerja Karyawan Menggunakan Metode Behaviorally Anchor Rating Scale (BARS) dan Management by Objectives (MBO) di Apotek X - Maharani, Anggun; Umam, Muhammad Isnaini Hadiyul; Kusumanto, Ismu; Nazaruddin, Nazaruddin; Suherman, Suherman (Universitas Batanghari Jambi, 2025)
This study aims to analyze the work assessment criteria that affect the quality of employee work, as well as provide solutions to improve employee performance. The methods used in this study are the Behaviorally Anchor Rating Scale (BARS) and Management By Objectives (MBO) methods. The results of this study found that there are 5 (five) factors that affect employee performance, namely attendance, work behavior, work quality, reliability, and managerial factors. These factors can be appreciated in the form of gifts, development such as skills training or improving certain abilities, and promotions. Therefore, the BARS method will provide the criteria that most affect employees, while the MBO method provides solutions to improve employees.